STABILITY AND CONDUCTIVITY OF BILAYER LIPID MEMBRANE IN PRESENCE Al_2O_3 NANOPARTICLES - Jomardyan, Tsovinar M.; Ananyan, Gayane V.; Arakelyan, Valery B. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
The effect of aluminum oxide nanoparticles (Al2O3) on the stability and conductivity of BLM (the bilayer lipid membrane) in solution was studied. It has been shown that Al2O3 nanoparticles increase the stability of BLM in an electric field, and BLM becomes more stable with increasing their concentration. The experimental data are analyzed in terms of the well-known theory of BLM stability, which is based on the concept of spontaneous formation of microscopic pores on the BLM, the development of which leads to the loss of BLM stability. It is shown that aluminum oxide nanoparticles increase the value of the coefficient of linear tension of the pore edge, and with an increase in the concentration of nanoparticles, the linear tension also increases. It has been shown that the presence of nanoparticles in the solution leads to a decrease in BLM conductivity.